Oral polio vaccine influences the immune response to BCG vaccination. A natural experiment. - Erliyani Sartono; Ida M Lisse; Elisabeth M Terveer; Paula J M van de Sande; Hilton Whittle; Ane B Fisker; Adam Roth; Peter Aaby; Maria Yazdanbakhsh; Christine S Benn (PLoS ONE)
Background Oral polio vaccine (OPV) is recommended to be given at birth together with BCG vaccine. While we were conducting two trials including low-birth-weight (LBW) and normal-birth-weight (NBW) infants in Guinea-Bissau, OPV was not available during some periods and therefore some infants did not receive OPV at birth, but only BCG. We investigated the effect of OPV given simultaneously with BCG at birth on the immune response to BCG vaccine. Methods and findings We compared the in vitro and the in vivo response to PPD in the infants who received OPV and BCG with that of infants who received BCG only. At age 6 weeks, the in vitro cytokine response to purified protein derivate (PPD) of M. Tuberculosis was reduced in LBW and NBW infants who had received OPV with BCG. In a pooled analysis receiving OPV with BCG at birth was associated with significantly lower IL-13 (p = 0.041) and IFN-gamma (p = 0.004) and a tendency for lower IL-10 (p = 0.054) in response to PPD. Furthermore, OPV was associated with reduced in vivo response to PPD at age 2 months, the prevalence ratio (PR) of having a PPD reaction being 0.75 (0.58-0.98), p = 0.033, and with a tendency for reduced likelihood of having a BCG scar (0.95 (0.91-1.00), p = 0.057)). Among children with a scar, OPV was associated with reduced scar size, the regression coefficient being -0.24 (-0.43-0.05), p = 0.012. Conclusions This study is the first to address the consequences for the immune response to BCG of simultaneous administration with OPV. Worryingly, the results indicate that the common practice in low-income countries of administering OPV together with BCG at birth may down-regulate the response to BCG vaccine.